Research of national identity in Georgian as a second language textbooks for ethnic minorities in the context of global education - Sabauri, Tinatin (American Journal of Education and Learning, 2025)
This study examines the representation of national identity in textbooks designed for teaching Georgian as a second language (GSL) to ethnic minority students, situating the analysis within the framework of global education. Using a mixed-methods design, the research combined textbook analysis with qualitative interviews and quantitative surveys. Twenty-four teachers and one educational expert were interviewed, and 283 graduates of Armenian- and Azerbaijani-speaking schools completed a questionnaire. The study explored how textbooks present national identity, how teachers incorporate cultural elements in instruction, and how students perceive their own identities and educational experiences. Findings reveal that many textbooks are misaligned with students’ linguistic competencies, often being either too difficult or too simplistic. Teachers highlighted the shortage of qualified staff and the need for additional bilingual and culturally relevant resources. Students reported mixed levels of interest in GSL lessons and identified language as a central marker of belonging, though many emphasized hybrid or primarily ethnic identities. The results underscore tensions between fostering Georgian national identity and respecting minority heritage. This study makes an original contribution by linking textbook analysis with perspectives from both teachers and students, offering evidence-based recommendations for curriculum reform, textbook development, and teacher training. It argues for a transcultural and inclusive approach to language education that supports both integration and diversity, thereby strengthening civic belonging in Georgia’s multi-ethnic society.